2018
DOI: 10.1021/acsnano.8b05718
|View full text |Cite
|
Sign up to set email alerts
|

Robust Bijels for Reactive Separation via Silica-Reinforced Nanoparticle Layers

Abstract: Pickering emulsions have been successfully used as media for catalysis and separation. However, simultaneous reaction and separation cannot be performed in a continuous mode in these systems, because reagents cannot be readily loaded into or recovered from the dispersed phase. Bicontinuous interfacially jammed emulsion gels (bijels), in which the oil and water phases are continuous throughout the structure, have potential as media for simultaneous reaction and separation in a continuous mode. In this work, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 30 publications
0
58
0
Order By: Relevance
“…Gel formation, a non-equilibrium approach, shows tremendous usefulness to form novel structures not achievable with traditional equilibrium approach [1][2][3][4] . In particular, the formation of bicontinuous structures through gelation processes has attracted extensive research interests due to their important applications in energy storage 5 , membrane science 6 , flow-through reaction 7 , and cell delivery 8 . One of the widely studied bicontinuous structure systems is the bicontinuous interfacially jammed emulsion gel (Bijel), which can form porous materials with tortuous channels by arresting the solvent spinodal decomposition with colloidal particles trapped at the interface of two phase-separating solvents 2,[9][10][11][12] .…”
mentioning
confidence: 99%
“…Gel formation, a non-equilibrium approach, shows tremendous usefulness to form novel structures not achievable with traditional equilibrium approach [1][2][3][4] . In particular, the formation of bicontinuous structures through gelation processes has attracted extensive research interests due to their important applications in energy storage 5 , membrane science 6 , flow-through reaction 7 , and cell delivery 8 . One of the widely studied bicontinuous structure systems is the bicontinuous interfacially jammed emulsion gel (Bijel), which can form porous materials with tortuous channels by arresting the solvent spinodal decomposition with colloidal particles trapped at the interface of two phase-separating solvents 2,[9][10][11][12] .…”
mentioning
confidence: 99%
“…One potential approach to overcome such a challenge is to induce convection in one or both liquid phases. A recent development has shown that bijels can be reinforced to withstand shear and flow 43 . By combining these recent advances in the preparation and application of bijels, we believe our current work brings us one step closer to realizing the vision of bijel-based continuous reactive separations.…”
Section: Discussionmentioning
confidence: 99%
“…AG TL conversion and LA yield of 46 %a nd 34 %, respectively,c an be achieved with productivities of 18 and 40 mmol (mol H + ) À1 As an alternative to emulsions,b ijels reinforced with silica can afford full conversion and high robustness in the base hydrolysis of ethyl acetate using NaOH (Figure 2d). [66] [63] b) Deacetalization; [64] c) Etherification; [65] D) hydrolysis; [66,67] e) Transesterification; [68][69][70][71] f) Alkylation/acylation; [72,73] g) Pechmannr earrangement. [74] Surface-active catalysts have been developed for biodiesel synthesis by transesterification of vegetable oils with methanol (MeOH) (Figure 2e).…”
Section: Acid-base Chemocatalysismentioning
confidence: 99%